2012
DOI: 10.1111/j.1570-7458.2011.01215.x
|View full text |Cite
|
Sign up to set email alerts
|

Methyl isonicotinate induces increased walking and take‐off behaviour in western flower thrips, Frankliniella occidentalis

Abstract: Timely detection of western flower thrips (WFT), Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae), is important to help prevent economic damage to crops. Coloured traps are commonly used for thrips monitoring and their efficacy can be markedly improved with the addition of semiochemicals such as methyl isonicotinate (MI). However, the behavioural response of thrips to these compounds is poorly understood. In leaf/petal disc laboratory experiments the effect of MI on adult female WFT was examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 37 publications
0
4
0
2
Order By: Relevance
“…The present study has shown that M. sjostedti responds to methyl‐isonicotinate, which is the active ingredient of Lurem‐TR, and confirms a previous report by Muvea et al The positive correlation observed with thrips attraction could be explained by frequent visits or longer stays of M. sjostedti in the device. Methyl‐isonicotinate has been reported to stimulate walking and take‐off behaviour in Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae) female adults . This may explain the finding of Niassy et al , who observed that conidial acquisition by F. occidentalis was greater in a Lurem‐TR‐baited device than in a device without Lurem‐TR.…”
Section: Discussionmentioning
confidence: 97%
“…The present study has shown that M. sjostedti responds to methyl‐isonicotinate, which is the active ingredient of Lurem‐TR, and confirms a previous report by Muvea et al The positive correlation observed with thrips attraction could be explained by frequent visits or longer stays of M. sjostedti in the device. Methyl‐isonicotinate has been reported to stimulate walking and take‐off behaviour in Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae) female adults . This may explain the finding of Niassy et al , who observed that conidial acquisition by F. occidentalis was greater in a Lurem‐TR‐baited device than in a device without Lurem‐TR.…”
Section: Discussionmentioning
confidence: 97%
“…Consequently, the second period was mainly focused on the effectiveness of MIN in commercial field conditions and different crops [ 23 , 25 , 26 , 27 , 31 , 32 , 43 , 45 , 47 , 48 , 67 , 68 , 86 , 87 , 88 , 89 , 90 ]. Regarding new naturally occurring attractant compounds, some promising candidates were identified, such as ( S )-(−)-verbenone, 3-hexen-1-ol, 2-phenylethyl acetate, nonanal, (±)-theaspirane and β-caryophyllene [ 43 , 91 , 92 , 93 ], and oviposition repellents, such as methyl salicylate, thymol, and carvacrol compounds [ 89 , 94 , 95 , 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, by 2022, this percentage increased to 4.8% of the total research volume in the literature on the semiochemicals associated with WFT (WoS on October 2022, n = 2104 articles). In addition to the low volume of research, it mainly converged in the study of a particular group of 4-pyridyl carbonyl compounds reported as attractants [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ] and the same sticky-trap types, usually square and blue [ 18 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…• De plantenstof methyl isonicotinaat is een attractant voor trips (van Tol et al 2012) (Davidson et al 2015), en is door Koppert op de markt gebracht als Lurem®.…”
Section: Inleidingunclassified
“…Gek genoeg kunnen dat soms dezelfde stoffen zijn. Zo is bekend dat de lokstof methyl isonycotinate (Lurem) ook het vlieggedrag van trips activeert (van Tol et al 2012). In deze studie werden sterke verschillen gevonden tussen het opvliegen van trips vanaf verschillende gewassoorten, waarbij trips sneller wegvloog vanaf bladponsjes van chrysant of paprika dan vanaf bladponsjes van een bonenplant.…”
Section: Inleidingunclassified